2017
DOI: 10.1093/mnras/stx1195
|View full text |Cite
|
Sign up to set email alerts
|

The structure of Andromeda II dwarf spheroidal galaxy

Abstract: We analyze in detail the spatial distribution and kinematic properties of two different stellar populations in Andromeda II (And II) dwarf spheroidal galaxy. We obtained their detailed surface density maps, together with their radial density profiles. The two populations differ not only in age and metallicity, but also in their spatial distribution and kinematics. Old stars ( 11 Gyr) follow a round distribution well fitted by truncated density profiles. These stars rotate around the projected optical major axi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 45 publications
(84 reference statements)
2
16
0
Order By: Relevance
“…Also, [57] shows that smaller galaxies tend to be more spherically symmetric and that dark matter distribution is more spherically symmetric than stellar distribution. Finally, although rotations are detected in several individual objects (see, e.g., [40, [58][59][60]), spectroscopic observations [61][62][63][64][65] show the absence of rotations with velocities comparable with the observed velocity dispersions in dSphs.…”
Section: Methodsmentioning
confidence: 99%
“…Also, [57] shows that smaller galaxies tend to be more spherically symmetric and that dark matter distribution is more spherically symmetric than stellar distribution. Finally, although rotations are detected in several individual objects (see, e.g., [40, [58][59][60]), spectroscopic observations [61][62][63][64][65] show the absence of rotations with velocities comparable with the observed velocity dispersions in dSphs.…”
Section: Methodsmentioning
confidence: 99%
“…In both cases, prolate rotation has been argued to be evidence for a recent merger. For example, the peculiar kinematics of And II may be due to a merger at z ∼ 1.75 (Amorisco, Evans & van de Ven 2014;Lokas et al 2014;del Pino et al 2017b;Fouquet et al 2017). In Phoenix, the spatial distribution of the young stars is aligned with the rotation axis/minor axis that is further evidence for a recent merger (Kacharov et al 2017).…”
Section: Search For Rotationmentioning
confidence: 99%
“…The full description and clustering process is described in del Pino et al (2017b), their section 3.…”
Section: Observationsmentioning
confidence: 99%
“…del Pino et al (2017b) found that approximately 40% of the stars may be part of different substructures, with 985 stars classified into 24 possible circular streams using a MCS = 13. This could indicate that Fornax is a rather complex system with various rotating components and its spheroidal shape is the superposition of stellar components with distinct kinematics (see their figure 13).…”
Section: Tidal Stirring Modelmentioning
confidence: 99%